Unlocking Methane Generation via Photo‐Thermal‐Coupled CO2 Hydrogenation by Integrating FeNiCrMnCo Multicomponent Alloy with GaN Nanowires - Muhammad Salman Nasir; Ying Zhao; Haotian Ye; Jinglin Li; Ping Wang; Ding Wang; Xinqiang Wang; Jun Song; Zhen Huang; Baowen Zhou (Advanced Science, 2025)
Abstract The exploration of a noble‐metal‐free photo‐thermal‐coupled catalytic architecture plays a vital role in solar‐driven conversion of carbon dioxide (CO2) into high‐value fuels and chemicals. In this study, FeNiCrMnCo multicomponent alloy (MCA) is integrated with GaN nanowires (NW's) for photo‐thermal‐coupled catalytic CO2 methanation. The MCA/GaN NW's nanohybrid demonstrates a considerable methane production rate of 199 mmol∙g−1∙h−1 with an impressive selectivity of 93% under white light irradiation of 3 W∙cm−2 at 290 °C by external heating. The turnover number approaches 20,160 mole CH4 per mole of MCA over a continuous operation period of 120 h, showcasing remarkable stability. Mechanistic investigations reveal that the unique MCA provides a flexible platform for tailoring the electronic and catalytic properties to optimize the adsorption and activation of CO₂ and H₂, thus leading to efficient and selective CO₂ methanation. This study presents an industry‐friendly architecture for photo‐thermal‐coupled CO2 hydrogenation into high‐value fuels and chemicals by coupling a noble‐metal‐free multicomponent alloy with GaN NWs, paving the way for advancements in sustainable energy conversion through CO2 utilization.